Lower regional cerebrovascular reactivity relates to worse episodic memory among older adults. (December 2021) - Robb, W. Hudson; Ahmed, Humza A.; Kim, Darcie S.; Landman, Bennett A.; Pechman, Kimberly R.; Gifford, Katherine A.; Donahue, Manus J.; Hohman, Timothy J.; Jefferson, Angela L.
Abstract: Background: Cerebrovascular reactivity (CVR) measures the ability of the cerebrovasculature to respond to vasoactive stimuli. Decreased CVR in the default mode network (DMN) has been associated with increased vascular risk factor burden. DMN connectivity is fundamentally dependent on vascular compliance, which can be altered in MCI, and may impact episodic memory consolidation. This study cross‐sectionally evaluated whether the topography of CVR is associated with episodic memory performance. Method: Vanderbilt Memory & Aging Project participants free of stroke were included (n=117, 76.0±7.3 years, 46% female). Participants underwent neuropsychological assessment and multimodal 3T brain MRI, including T1 ‐weighted imaging and T2 * ‐ weighted blood‐oxygenation level‐dependent (BOLD‐fMRI) for quantifying CVR. During the BOLD‐fMRI acquisition, a hypercapnic normoxic respiratory challenge was administered by alternating normocapnic normoxia and hypercapnic normoxia (5% CO2 /95%‐air) in 90s blocks. BOLD‐fMRI data were time‐delay processed, yielding whole‐brain mapping of the maximum correlation with the gas stimulus (CVRMAX ) and time‐to‐max CVR (CVRDELAY ). Mean CVR metrics were calculated in atlas‐derived DMN regions. Ordinary least squares regression models related DMN‐CVR to episodic memory performance adjusting for demographics, Framingham Stroke Risk Profile, and apolipoprotein E‐e4 status. Clusters were corrected using family‐wise‐error rate p<0.05. Result: DMN‐CVRMAX was related to episodic memory performance (b=1.0x10 ‐3, p=0.03) but DMN‐CVRDELAY was not (p=0.09). In voxelwise analysis relating CVRMAX to memory, seven clusters surviving correction were identified, all suggesting lower CVRMAX related to worse memory performance. The peak value of the top cluster was located in the middle temporal gyrus. In voxelwise analysis relating CVRDELAY to memory, 11 clusters surviving correction were identified, all indicating longer CVRDELAY related to worse memory performance. The peak value of the top cluster was located in postcentral gyrus. Conclusion: Among older adults, lower DMN‐CVRMAX is associated with worse episodic memory performance and this association is not confined to the DMN. Associations between regionally reduced vascular compliance and episodic memory may result from vascular impairment of large‐scale brain networks such as the DMN, though these associations should be further explored. T32‐AG058524, IIRG‐08‐88733, R01‐AG034962, R01‐NS100980, K24‐AG046373, P20‐AG068082